Assessing the EU Energy (In)Dependency on Conventional Resources in Times of War - Andrei-Teofil Postolachi; Stefan-Catalin Topliceanu (Ovidius University Annals: Economic Sciences Series)
International economic and geopolitical changes caused by the war between Russia and Ukraine have intensified the EU member countries' concerns about the supply of energy resources and its energy security. The aim of the paper is to highlight the differences between EU countries in terms of energy dependence on conventional resources, mainly natural gas, petroleum products and fossil fuels. The research methodology implies a composite index applied for the period 2014- 2022. The results show that there are three dimensions of energy dependence for EU countries, such as internal consumption and external supply (D1), self-sustaining capacity with natural gas (D2), and self-sustaining capacity with fossil fuels (D3). Germany, Italy and France have a high degree of energy dependence, while countries such as Poland, Romania and the Netherlands have a low level. These differences between EU countries show that the EU's energy security objectives should focus on renewable energy sources.